Preparation and Characterization of Breathable Hemostatic Hydrogel Dressings and Determination of Their Effects on Full-Thickness Defects - Pan, Hong (Polymers (Basel), 2017)
Hydrogel-based wound dressings provide a cooling sensation, a moist environment, and act as a barrier to microbes for wounds. In this study, a series of soft, flexible, porous non-stick hydrogel dressings were prepared through the simple repeated freeze-thawing of a poly(vinyl alcohol), human-like collagen (or and carboxymethyl chitosan) mixed solution rather than chemical cross-linking and Tween80 was added as pore-forming agent for cutaneous wound healing. Some of their physical and chemical properties were characterized. Interestingly, hydrogel PVA-HLC-T80 and PVA-HLC-CS-T80 presented excellent swelling ratios, bacterial barrier activity, moisture vapor permeability, hemostasis activity and biocompatibility. Furthermore, in vivo evaluation of the healing capacity of these two hydrogels was checked by creating a full-thickness wound defect (1.3 cm × 1.3 cm) in rabbit. Macroscopic observation and subsequent hematoxylin eosin staining (H&E) staining and transmission electron microscopy (TEM) analysis at regular time intervals for 18 days revealed that the hydrogels significantly enhanced wound healing by reducing inflammation, promoting granulation tissue formation, collagen deposition and accelerating re-epithelialization. Taken together, the obtained data strongly encourage the use of these multifunctional hydrogels for skin wound dressings.